Minsky's cushions of safety: Systemic risk and the crisis in the US subprime mortgage market - Jan Kregel (Levy Economics Institute of Bard College, 2008)
In this brief, Senior Scholar Jan Kregel reviews Hyman P. Minsky's concept of financial fragility - in short, that the structure of a capitalist economy becomes more fragile over a period of prosperity - and concludes that the current crisis is in fact the result of insufficient margins of safety based on how creditworthiness is assessed in the new originate and distribute financial system.
Keywords: 330; Kreditrisiko; Bankenkrise; Finanzmarktkrise; Systemrisiko; USA